Simulating protostellar evolution and radiative feedback in the cluster environment - Klassen, Mikhail; Pudritz, Ralph E.; Peters, Thomas (Monthly notices of the Royal Astronomical Society, 2012)
Abstract. Radiative feedback is among the most important consequences of clustered star formation inside molecular clouds. At the onset of star formation, radi